2018
DOI: 10.4067/s0717-95022018000401161
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations of Muscle Tissue of Rats Submitted to Aerobic and Anaerobic Physical Training in Different Ergometer Models

Abstract: The objective of the present study was to analyze the effects of four different training models, two aerobic and two anaerobic models, in relation to muscular hypertrophy, by means of morphometric analysis of the muscle cells of the soleus muscle and the extensor digitorum longus muscle (EDL). The animals were divided into five groups, control (C), aerobic training in swimming (ATS), resistance training in water (RTW), aerobic training on a treadmill (ATT), and resistance training in climbing (RTC). The aerobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…5,7,18,19 The greater the intensity of the exercise, the greater the stimulus for hypertrophy, promoting greater stimulus to the protein synthesis of the contractile elements responsible for muscle contraction, generating an increase in the volume of muscle fiber. 5,6,17 The muscle hypertrophy process is modulated by the mechanical stimulus to which the muscle tissue is submitted, so an exercise with greater overload will promote greater stimulus for muscle hypertrophy. 20 In addition, a study carried out with exercise on a stationary exercise bike 21 that the stimulus for the hypertrophy pathway, and increase in the glucose transporter (GLUT4), occurred with greater magnitude in type II muscle fibers, than in type I muscle fibers, a fact that could explain the hypertrophy observed only in type II fibers in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…5,7,18,19 The greater the intensity of the exercise, the greater the stimulus for hypertrophy, promoting greater stimulus to the protein synthesis of the contractile elements responsible for muscle contraction, generating an increase in the volume of muscle fiber. 5,6,17 The muscle hypertrophy process is modulated by the mechanical stimulus to which the muscle tissue is submitted, so an exercise with greater overload will promote greater stimulus for muscle hypertrophy. 20 In addition, a study carried out with exercise on a stationary exercise bike 21 that the stimulus for the hypertrophy pathway, and increase in the glucose transporter (GLUT4), occurred with greater magnitude in type II muscle fibers, than in type I muscle fibers, a fact that could explain the hypertrophy observed only in type II fibers in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…18 Aerobic exercise is best known for promoting improvement in oxidative capacity, increased blood perfusion, and the number of mitochondria, generating greater resistance to fatigue. 3,6 A review study looked at the effectiveness of aerobic training for gaining muscle hypertrophy, and found that there is hypertrophy when the exercise is performed over the long term (9 to 12 weeks). 22 In the current study, only 4 weeks of training were performed, so the training time may have been decisive for the non-adaptation of the slow-twitch muscles to exercise.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations